Conflict Management Skills Development in Education Transformation for Teachers of SMA Negeri 13 Ambon : Pengembangan Kemampuan Manajemen Konflik dalam Transformasi Pendidikan bagi Guru SMA Negeri 13 Ambon - Ayhuan, Welhelmina Febriana; Satori, Djam'an; Nurdin, Diding; Meirawan, Danny (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
SMA Negeri 13 Ambon, as one of the driving schools in Ambon City, is currently sustaining to carry out transformation efforts comprehensively. This effort certainly raises many sources of conflicts, which, if managed properly, will actually become constructive conflicts that encourage the transformation process. Unfortunately, conflict that happened internally in the school is regarded negative by most of the teachers at the school and actually eventually hinder the transformation process at school. This has a great impact on the teacher's lack of ability to manage conflict in the school. Through the program of Musyawarah Guru Mata Pelajaran (MGMP), teachers are equipped with the correct understanding of conflict and how to manage conflict appropriately so that it is beneficial for the transformation process at SMA Negeri 13 Ambon.